Arquivo Público do Amazonas: uma trajetória de memórias, esquecimentos e descasos (1852-1999) - (:unkn) unknown (Universidade Federal do Amazonas, 2016)
This dissertation sought to build knowledge about the political and administrative trajectory of the Public Archive of Amazonas, an important centenary institution for historical research, located in the Historic Center of Manaus. The public archive can be understood as a practice of the State and of society as a whole, not being safe from crises, abandonment and uncertainty, as well as from imagination, innovation and action. The study of a public archive does not lead us to speak about an institution in itself, but it also involves historical subjects in articulation with their social contexts, producing, organizing, guarding and preserving documents permeated by speeches, memories, identities, trajectories, struggles, agreements , negotiations, etc. Emerging and systematizing information about this institution from historical sources required patient reading and methodology. Installed in 1852 and called the Archive of the Province, it survived among the regulations that organized and reorganized the Secretariat of the Government, going through several difficulties of functioning. In 1897 he disassociated himself from this division, being officially created through decree nº. 184, of August 19 of the same year, now called Public Archives. The most relevant aspects of its trajectory were raised in three moments: that of its installation; that of its creation; and the move to the final seat; perceiving the treatment he received from the public administration, as the practices of the historical agents who worked in this place marked both the government activities and those of its users; and the difficulties encountered by its administrators for its organization and conservation, regarding the physical space, maintenance of the collection and human resources.
Amazonas Public Archive: a trajectory of memories, forgetfulness and neglect (1852-1999)
Keywords: Arquivos públicos; Arquivo da Província; Documentos históricos; Centro Histórico de Manaus; Preservação documental; CIÊNCIAS HUMANAS; Arquivo Público do Amazonas; Historiografia; Administração Pública